(untitled) (Journal of actual problems of jurisprudence, 2021)
The article is a result of the conducted research, devoted to a participant of criminal proceedings, as a private prosecutor, the procedural order of the main trial in cases of private prosecution is considered. The article reveals some peculiarities of court proceedings, such as reconciliation of an injured person with a guilty person, which allows to eliminate the conflict between them and normalize the situation. Private prosecution has an important procedural value, as it allows to clearly define a specific moment of the beginning of the trial, which in turn provides control over the procedural timing of the proceedings, as well as the possibility of exercising their rights by all interested persons within the framework of their legal status. At this point, the participants in the process acquire a certain procedural status and are endowed with the relevant procedural rights and obligations. In order to terminate such criminal cases in connection with the reconciliation of the victim with the accused, it is not enough just to express the will of the parties, as well as to compensate the guilty person for the damage caused to the victim. At the same time, a criminal case may be terminated only in respect of a person brought to justice for the first time. However, compliance with all the conditions specified in the law does not mean the unconditional termination of the criminal case. Termination of a criminal case in order to reconcile the parties is the right, not the duty of the court. Keywords: private prosecutor, trial, defendant, private prosecution cases, judge, sentence, Institute of reconciliation of the parties.